Answer:
x = - 3, x = 6
Explanation:
x² - 3x - 18 = 0 ( add 18 to both sides )
x² - 3x = 18
To complete the square
add ( half the coefficient of the x- term )² to both sides
x² + 2(-
)x +
= 18 +
![(9)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/5fny6pwbbk4iexcfll2nrfuc2hngemuq6k.png)
(x -
)² =
( take square root of both sides )
x -
= ±
= ±
( add
to both sides )
x =
±
![(9)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/gciihs38gxehqdm6smr0otlf28uz1s1efj.png)
Then
x =
-
=
= - 3
x =
+
= 6